Evaluation Analysis of OCR and GFR Relay Protection Coordination on Feeder YB-02 PT PLN ULP Natal with ETAP Simulation - Tharo, Zuraidah; Anisah, Siti; Putra, Fariz Aditya; Andriana, Melly (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
With the increasing number of customers of PT. PLN (Persero) ULP Natal, disruption to the distribution system will result in more widespread blackouts. To avoid this, the protection system in the distribution channel (especially in the YB-02 feeder) needs to be evaluated to ensure proper coordination. The protection systems are outgoing PMT, Recloser L-01 and Recloser L-02. The method used in this study is a method of observation, literature study, interviews and guidance. From this study, it was found that the coordination conditions between PMT Outgoing, Recloser L-01 and Recloser L-02 were correct and their capabilities could be improved by calculating the OCR and GFR relay settings. The coordination between PMT Outgoing.